A Twenty-first Century Socialist Agriculture? Land Reform, Food Sovereignty and Peasant–State Dynamics in Venezuela - Lavelle, Daniel (The International Journal of Sociology of Agriculture and Food, 2014)
This article examines state–peasantry dynamics in Venezuela in regards to the formation, implementation and contestation of land reform and agricultural policy. As a self-proclaimed socialist state, the Chávez Government has framed its agrarian policies as a reordering of the food system that prioritizes land redistribution, smallholder agriculture, and sustainable forms of production. Yet, despite an apparently positive policy context, rural dynamics have been characterized by conflict over land and a geographically and temporally uneven process of policy implementation in rural areas. This article examines how peasants have engaged with Venezuela’s land reform processes and their role in shaping the character and scope of state policy. In particular, it investigates the dynamics of technically illegal peasant occupation of estates in a seemingly ‘pro-peasant’ policy context. Peasant–state dynamics are analysed through the lens of food sovereignty, where land reform processes and struggles represent contestation over conceptions of what constitutes ‘appropriate’ production in a ‘socialist’ agricultural regime.